Disrupted Communication: Understanding How Bullying-Related Anxiety Interferes with Students' Speaking Class Proficiency - Syahruddin M; Rosmawati Abdul Maing; Darmawati Azis Bausad; M Dahlan Bahang; A. Rizal (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Bullying remains a persistent issue in educational settings, with serious consequences for students’ emotional well-being and academic engagement. This study examines the impact of bullying on students’ willingness to speak, identifies the specific aspects of speaking most affected, and explores the coping strategies employed by victims. A qualitative descriptive case study was conducted with five purposively selected students who had experienced bullying. Data were gathered through semi-structured interviews to explore the students’ classroom anxiety in depth. The findings reveal that bullying-induced anxiety significantly reduces students’ willingness to participate in classroom discussions and impairs their verbal communication skills, particularly pronunciation, vocabulary use, and overall confidence. Coping responses varied, with some students relying on self-affirmation while others adopted proactive strategies to manage their anxiety, highlighting the complexity of individual adaptation. This study, though limited to a small sample, provides valuable insights into the nuanced experiences of bullying victims in a higher education context. The results emphasize the importance for English language educators to create supportive classroom environments, implement anxiety-reducing speaking activities, and for institutions to develop anti-bullying initiatives. These implications contribute to both pedagogical practice and policy development aimed at fostering inclusive and resilient learning spaces.